2019
DOI: 10.36740/wlek201903107
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nonalcoholic Fatty Liver Disease With Small Intestine Bacterial Overgrowth in Obese Children

Abstract: Introduction: In recent years, NAFLD is considered as the key of the so-called metabolic inflammation, in which the intestinal microbiota plays an important role. The aim: To determine the effect of small intestine bacterial overgrowth on the liver structural and functional parameters in children with obesity and overweight. Materials and methods: The object of the study was 89 children with obesity/overweight. Depending on the presence of SIBO based on the results of the hydrogen breath test with glucose, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Some studies show that the prevalence of SIBO in patients with chronic nonalcoholic liver disease can be as high as 35% of the total population, and the prevalence increases with the percentage of men in the population [88,94,95]. Other research suggests that there might be an association between NAFLD and SIBO in children [94,96,97]. Future studies should explore the mechanisms linking SIBO and NAFLD and examine whether treating SIBO could prevent NAFLD in children.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies show that the prevalence of SIBO in patients with chronic nonalcoholic liver disease can be as high as 35% of the total population, and the prevalence increases with the percentage of men in the population [88,94,95]. Other research suggests that there might be an association between NAFLD and SIBO in children [94,96,97]. Future studies should explore the mechanisms linking SIBO and NAFLD and examine whether treating SIBO could prevent NAFLD in children.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…Future studies should explore the mechanisms linking SIBO and NAFLD and examine whether treating SIBO could prevent NAFLD in children. The analysis of risk factors of SIBO in children showed that metabolic syndrome and NAFLD as the risk factors for SIBO development [94,96,97].…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
See 1 more Smart Citation
“…The association of NAFLD with SIBO in obese and overweight children has also been studied [97][98][99]. A meta-analysis [100] was conducted based on the three previously mentioned studies, involving 205 children, which indicated a possible relationship between SIBO and NAFLD in children.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…A meta-analysis of three studies showed that children with SIBO were more likely to have MAFLD (OR = 5.27; 95%CI: 1.66-16.68) and children with MAFLD were at an increased risk of developing SIBO (RR = 2.17; 95%CI: 1.54-2.81)[ 84 ]. Metabolic syndrome and MAFLD were risk factors for SIBO development in obese children[ 85 ].…”
Section: Liver Diseasesmentioning
confidence: 99%